2013
DOI: 10.1111/cas.12101
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐angiogenic and anti‐tumor effects of TAK‐593, a potent and selective inhibitor of vascular endothelial growth factor and platelet‐derived growth factor receptor tyrosine kinase

Abstract: We recently reported that TAK-593, a novel imidazo [1,2-b]pyridazine derivative, is a highly potent and selective inhibitor of the vascular endothelial growth factor (VEGF) and platelet derived growth factor (PDGF) receptor tyrosine kinase families. Moreover, TAK-593 exhibits a uniquely long-acting inhibitory profile towards VEGF receptor 2 (VEGFR2) and PDGF receptor b (PDGFRb).In this study, we demonstrated that TAK-593 potently inhibits VEGF-and PDGF-stimulated cellular phosphorylation and proliferation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Angiogenesis is critical for tumor growth and progression, because it forms a network of blood vessels which penetrate into cancer growth to supply nutrients and oxygen and to remove metabolic waste from the tumor. Therefore, tumor growth and metastasis are highly dependent upon the angiogenic process 1 , implying that anti-angiogenic drugs may be important in the cancer therapy 2 . Indeed, anti-angiogenic agents have been proven to inhibit the growth of a wide variety of solid tumors in animal models by reducing tumor blood supply 3 .…”
mentioning
confidence: 99%
“…Angiogenesis is critical for tumor growth and progression, because it forms a network of blood vessels which penetrate into cancer growth to supply nutrients and oxygen and to remove metabolic waste from the tumor. Therefore, tumor growth and metastasis are highly dependent upon the angiogenic process 1 , implying that anti-angiogenic drugs may be important in the cancer therapy 2 . Indeed, anti-angiogenic agents have been proven to inhibit the growth of a wide variety of solid tumors in animal models by reducing tumor blood supply 3 .…”
mentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a potent mediator of angiogenesis that induces the formation of novel blood vessels, and growth and metastasis of cancers. Several researches have revealed that VEGF plays an important role in promoting endothelial cell proliferation and migration, and induces a direct effect on cancer proliferation and invasiveness (Awazu et al 2013;Hu et al 2013;Sun et al 2014). It has been reported that TBC domain containing proteins also participate in cancer proliferation and angiogenesis via VEGF (Kim et al 2003;Ji et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The growth and spread of tumors depends on the formation of an adequate vascular support and amoeboid mode of tumor cell invasion (9). Furthermore, several studies have indicated that VEGF serves a role in promoting endothelial cell proliferation and migration, and induces a direct effect on cell proliferation and invasiveness (3,10,11). Previous studies have indicated that suppressing the expression or activity VEGF in ovarian cancer cells may represent a potential anticancer therapy (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%